The Sociocultural Adaptation of Family Weavers on Nusa Penida Island - Diaz Restu Darmawan; Taufik Agus Purnomo; Putu Karina Pravitasari (Faculty of Social Science, Universitas Negeri Malang, 2026)
Rangrang cloth is a local fabric that is produced according to the traditional knowledge of the people of Nusa Penida Island. This traditional knowledge has been transmitted through generations by virtue of a process of inheritance. The weaving patterns of Rangrang cloth are imbued with the rich cultural narratives of the island's inhabitants, offering a subtle reflection of the community's way of life. However, the practice of weaving Rangrang cloth is gradually diminishing. This phenomenon is influenced by a variety of factors, including changes in the Indonesian textile market and the rapid development of tourism in Nusa Penida since 2020. As a result, it compels weavers to implement various modifications as a means of adapting to the livelihood system that has been passed down through family inheritance. The present study yielded various forms of change. To ensure the accuracy of the data collected, this research process will employ qualitative research methods, with a particular focus on direct observation in Pejukutan village and Tanglad village. The purposive sampling method was then employed to augment the data presented in the article's narrative which was taken from two families who are active as weavers. This will facilitate the subsequent data analysis and reduction process. This article presents a concise ethnographic account of the life experiences of two weaver families residing on the island of Nusa Penida.